2020
DOI: 10.1177/1368430220959710
|View full text |Cite
|
Sign up to set email alerts
|

Can past intergroup contact shape support for policies in a pandemic? Processes predicting endorsement of discriminatory Chinese restrictions during the COVID-19 crisis

Abstract: A survey of 340 UK residents was conducted when the COVID-19 virus first reached the UK in February 2020. We measured past experiences of positive and negative intergroup contact with Chinese people as predictors of intergroup threat and emotions in the context of the pandemic; and how these processes in turn predicted support for discriminatory policies designed to restrict the freedom of Chinese people in the UK. We tested a novel threat-matching hypothesis which draws upon models of outgroup-specific social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Other protagonists were also frequently perceived as salient; some who were also trying to actively manage the pandemic (e.g., political entities, such as governments, medical expert advisors, and NGOs); and some who were disproportionately affected by the pandemic (e.g., vulnerable groups, such as elderly and youth). Interestingly, no protagonist was nominated who were perceived to be partially responsible for the health crisis in other studies (e.g., (16). Yet, which of these protagonists emerged as relevant was far less universal across nations -a finding which we were only able to observe thanks to our participant-led nomination approach and coverage of 35 country contexts.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Other protagonists were also frequently perceived as salient; some who were also trying to actively manage the pandemic (e.g., political entities, such as governments, medical expert advisors, and NGOs); and some who were disproportionately affected by the pandemic (e.g., vulnerable groups, such as elderly and youth). Interestingly, no protagonist was nominated who were perceived to be partially responsible for the health crisis in other studies (e.g., (16). Yet, which of these protagonists emerged as relevant was far less universal across nations -a finding which we were only able to observe thanks to our participant-led nomination approach and coverage of 35 country contexts.…”
Section: Discussionmentioning
confidence: 63%
“…For instance, more benevolent social perceptions of elderly, vulnerable protagonists disproportionately affected by the pandemic were associated with more containment behaviors in Italy during the COVID-19 pandemic (15). The less benevolent the perception of Chinese (protagonists perceived to be partially responsible for the pandemic), the more the endorsement for restriction policies in a UK sample (16). Lastly, it has been suggested that trust in institutions, such as governments, and health experts positively predicts compliance with measures recommended by these institutions (17)(18)(19).…”
Section: Introductionmentioning
confidence: 96%
“…Another curious finding was the lack of a significant main effect of intergroup contact on less support for anti-Asian travel policy. This finding is somewhat unexpected given recent work from the UK showing that prior positive intergroup contact with Chinese people was associated with less support for anti-Chinese discriminatory policies among White British citizens during the COVID-19 pandemic (Alston et al, 2020). One possible reason for the difference in results concerns the particular measures used to assess support for discriminatory policies.…”
Section: Discussionmentioning
confidence: 73%
“…Recent research has explored the consequences of COVID‐19 threat with regards to intergroup relations (see Schaller et al, 2021 ). With the virus thought to have originated in China, initial studies demonstrated positive correlations, in cross‐sectional datasets, between perceived COVID‐19 threat and anti‐Asian attitudes and support for discriminatory Chinese restrictions (Alston et al, 2020 ; Reny & Barreto, 2020 ). However, COVID‐19 threat has also been shown to lead to negative perceptions of stigmatized outgroups that are not directly associated with the virus.…”
Section: Introductionmentioning
confidence: 99%